2002
DOI: 10.1212/wnl.59.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of albuterol in spinal muscular atrophy

Abstract: The aim of this pilot study was to evaluate the effect of albuterol in children with spinal muscular atrophy (SMA). Thirteen patients (five with SMA II and eight with SMA III) were given oral albuterol for 6 months. There was a significant increase in myometry, forced vital capacity, and lean body mass between the baseline and the 6-month assessments (p < 0.05). Albuterol may have a beneficial effect in patients with SMA without causing any significant adverse effects. Larger randomized, placebo-controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 8 publications
4
56
0
Order By: Relevance
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin, a likely neuroprotective agent, did not lead to differences in the outcome measure, 12 whereas, in pilot trials using thyrotropin-releasing hormone and albuterol, improvement of muscle strength in a small number of type II and III patients has been reported. 13,14 None of these drugs appears to act on the molecular defect. Essentially two strategies to increase SMN2 fl transcripts can be envisaged: one leading to the upregulation of the SMN2 genes and the other resulting in the modification of the SMN2 mRNA splicing pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In an open label pilot trial with thirteen SMA type II and III patients, there was a significant increase in muscle strength measured by myometry and forced vital capacity (FVC) after six months of salbutamol treatment. The therapy was well tolerated, but in several patients an increase in contractures was seen that may have been due to a stronger effect of salbutamol on agonist muscles [115]. In another open trial on 23 SMA type II patients, the functional scores were significantly higher after 6 and 12 months of treatment with salbutamol and there were no major side effects [116].…”
Section: Thyrotropin Releasing Hormone (Trh) Hasmentioning
confidence: 96%